Catastrophe Compassion: Understanding and Extending Prosociality Under Crisis. Issue 8 (August 2020) - Zaki, Jamil
Abstract : How do people behave when disasters strike? Popular media accounts depict panic and cruelty, but in fact individuals often cooperate with and care for one another during crises. I summarize evidence for such 'catastrophe compassion', discuss its roots, and consider how it might be cultivated in more mundane times.